PROBLEMS OF STUDYING POLYSEMOUS VERBS OF THE RUSSIAN LANGUAGE IN FOREIGN LANGUAGE GROUPS OF HIGHER EDUCATIONAL INSTITUTIONS (ON THE EXAMPLE OF INTERACTIVE METHODS) - Касымова Феруза Суннатовна (Bright Mind Publishing, 2025)
This article is devoted to the problems of studying polysemous verbs by students of foreign language groups, the relevance of this issue. Attention is paid to the types of innovations that contribute to the effective study of these verbs, special attention is paid to the technology "Thick and Thin Questions".